The prevalence of hyposalivation in type 2 diabetes mellitus patients at Endocrinology Department, Internal Medicine Sub Department of RSUP Dr Hasan Sadikin Bandung - Sundari, Marini; Dewi, Tenny Setiani; Natalia, Nanny (Universitas Padjadjaran, 2013)
Introduction: The salivary flow rate reduces Hyposalivation. Type 2 diabetes mellitus patient with hyposalivation have a high risk of various oral complications if untreated adequately. The aim of this study was to find the prevalence of hyposalivation in type 2 diabetes mellitus patient at RSUP Dr Hasan Sadikin Bandung. Methods: This study was a descriptive observational with a cross-sectional approach and consecutive sampling method to 30 samples. The study was performed with objective assessment through measuring the unstimulated salivary flow of the whole saliva using spitting method for 5 minutes. Results: The result of this study shows that the prevalence of hyposalivation on type 2 diabetes mellitus patient is 10%. The mean of salivary flow rate sample with hyposalivation is 0,07 mL/minute. Conclusion: The conclusion of this study shows a low prevalence of hyposalivation in type 2 diabetes mellitus patients at RSUP Dr Hasan Sadikin Bandung in October 2011.